COVID-19 testing, case, and death rates and spatial socio-demographics in New York City: An ecological analysis as of June 2020. (March 2021) - Kim, Byoungjun; Rundle, Andrew G.; Goodwin, Alicia T.Singham; Morrison, Christopher N.; Branas, Charles C.; El-Sadr, Wafaa; Duncan, Dustin T.
Abstract: We assessed the geographic variation in socio-demographics, mobility, and built environmental factors in relation to COVID-19 testing, case, and death rates in New York City (NYC). COVID-19 rates (as of June 10, 2020), relevant socio-demographic information, and built environment characteristics were aggregated by ZIP Code Tabulation Area (ZCTA). Spatially adjusted multivariable regression models were fitted to account for spatial autocorrelation. The results show that different sets of neighborhood characteristics were independently associated with COVID-19 testing, case, and death rates. For example, the proportions of Blacks and Hispanics in a ZCTA were positively associated with COVID-19 case rate. Contrary to the conventional hypothesis, neighborhoods with low-density housing experienced higher COVID-19 case rates. In addition, demographic changes (e.g. out-migration) during the pandemic may bias the estimates of COVID-19 rates. Future research should further investigate these neighborhood-level factors and their interactions over time to better understand the mechanisms by which they affect COVID-19. Highlights: Neighborhood-level COVID-19 rates may suffer from biased population estimates due to residents moving out. This is the first study to address the differential out-migration rates across neighborhoods in New York city. The out-migration measure was positively associated with COVID-19 case rates. Lower housing density in a neighborhood was associated with a higher COVID-19 case.